2015
DOI: 10.3389/fnins.2015.00010
|View full text |Cite
|
Sign up to set email alerts
|

Switched-capacitor realization of presynaptic short-term-plasticity and stop-learning synapses in 28 nm CMOS

Abstract: Synaptic dynamics, such as long- and short-term plasticity, play an important role in the complexity and biological realism achievable when running neural networks on a neuromorphic IC. For example, they endow the IC with an ability to adapt and learn from its environment. In order to achieve the millisecond to second time constants required for these synaptic dynamics, analog subthreshold circuits are usually employed. However, due to process variation and leakage problems, it is almost impossible to port the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Compared to neuromorphic approaches, all memristive approaches are several orders of magnitude better (Azghadi et al, 2014 ). In terms of absolute area, the BFO memristor is comparable to some neuromorphic implementations (Hasler and Marr, 2013 ; Noack et al, 2015 ), but not competitive with memristor crossbar devices, as we are employing a single device test structure that has a large contact size for reasons of convenience. However, BFO device scaling is well established, thus we can aggressively scale the size of the top electrode to 10 μm 2 and the thickness of the BFO to 100 nm (Jin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to neuromorphic approaches, all memristive approaches are several orders of magnitude better (Azghadi et al, 2014 ). In terms of absolute area, the BFO memristor is comparable to some neuromorphic implementations (Hasler and Marr, 2013 ; Noack et al, 2015 ), but not competitive with memristor crossbar devices, as we are employing a single device test structure that has a large contact size for reasons of convenience. However, BFO device scaling is well established, thus we can aggressively scale the size of the top electrode to 10 μm 2 and the thickness of the BFO to 100 nm (Jin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a switched-capacitor realization of synapses in 28 nm CMOS was developed (Noack et al, 2015), which minimizes the leakage current problems present when CMOS-based architectures are scaled down in size. However, this system requires 0.36 mm 2 area and a power consumption of 1.9 mW for only 128 presynapses and 8,192 “stop-learning” synapses which corresponds to roughly 2.27 × 10 4 synapses/mm 2 and an energy requirement of 0.23 nJ to 0.23 mJ per synapse.…”
Section: Discussionmentioning
confidence: 99%
“…The spike-timing dependent plasticity (STDP) synaptic learning rule, inspired from the behavior of the biological neural system (Dayan and Abbott, 2001) and dominant in the brain, has been proposed and experimentally demonstrated with memristors acting as synapses by several groups over the past few years in many material systems, such as oxides (Yu et al, 2011; Wang et al, 2012a,b, 2016; Wu et al, 2012; Pickett et al, 2013; Mandal et al, 2014; Kim et al, 2015), chalcogenides (Li et al, 2013b; Mahalanabis et al, 2014a,b, 2016; La Barbera et al, 2015), silicon (Jo et al, 2010; Subramaniam et al, 2013), organic materials (Alibart et al, 2012; Li et al, 2013a; Cabaret et al, 2014; Luo et al, 2015), and even magnetic tunnel junctions (Krzysteczko et al, 2012). Illustrations of memristor effectiveness have also been shown in simulation and with transistor and/or complementary metal oxide semiconductor (CMOS)-based memristors (Rachmuth et al, 2011; Rose et al, 2011a,b; Cruz-Albrecht et al, 2012; Noack et al, 2015) and graphics processing units (Snider et al, 2011). The exploration of new memristor materials systems is driven by the advantage of analog, memristor-based learning implementations compared to the digital-based learning, where the analog, memristor-based learning was shown to provide an improvement of at least a factor of 10 for power and density (Rajendran et al, 2013) over digital-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…The OTA-C approach uses a transconductance to emulate an RC decay [3], [4]. In deep submicron technologies, solutions have to be found that rely less on analog performance, such as a switched capacitor charge sharing emulating an exponential decay [5]. However, the above approaches have four main drawbacks.…”
Section: Introductionmentioning
confidence: 99%